Solvent-free rapid synthesis of porous CeWOx by a mechanochemical self-assembly strategy for the abatement of NOx. Issue 14 (26th March 2020) - Liu, Jixing; Cheng, Huifang; Tan, Junbin; Liu, Bing; Zhang, Zihao; Xu, Haidi; Zhao, Minjie; Zhu, Wenshuai; Liu, Jian; Zhao, Zhen
Abstract : Porous CeWO x catalysts with impressive specific surface areas and deNO x activity were constructed by a rapid and solvent-free strategy. Abstract : Herein, we designed and initiated a novel mechanochemical self-assembly protocol that realized a rapid and solvent-free construction of a series of highly porous CeWO x oxides with high specific surface areas up to 143 m 2 g −1, and their catalytic activities were examined for selective catalytic reduction of NO x with NH3 (NH3 -SCR). Experimental results revealed that Ce0.8 W0.2 O x exhibited the broadest activity temperature window for NO x abatement (210–440 °C) and excellent resistance to SO2 and H2 O poisoning under a high gas hour space velocity (GHSV = 125 000 h −1 ) on account of its high specific surface area, abundant acid and redox sites, as well as more exposed active sites. DFT calculations unveiled that the amount of W dopant significantly influenced the structure of active sites, and that Ce0.8 W0.2 O x exhibited the lowest oxygen vacancy formation energy (0.84 eV) and the strongest NH3 binding ability (−1.55 eV). Furthermore, kinetics experimental results disclosed that the incorporation of mesopores into CeWO x induced the exposure of more active sites, thereby facilitating the access of reactants to more active sites and the adsorption and activation of ammonia species, thereafter promoting the catalytic performance of CeWO x catalysts. Therefore, this work not only introduces a new opportunity for fabricating a number of advanced porous materials, but also provides insight into the crucial role of mesopores and dopants in heterogeneous catalysis reactions.